The Use of ELSA Speak Application to Improve Pronunciation Accuracy of Ninth Graders at SMPN 1 Gondang - Ayuk Puput Wilujing; Dina Karikawati (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
This study examines the effectiveness of the ELSA Speak application in improving the English language skills of ninth-grade students at SMPN 1 Gondang. The problem addressed is students' pronunciation skills. The purpose of this study was to understand the learning growth before and after the use of the application, as well as to assess the value of technology in English teaching. This study used a quantitative approach with a pre-experimental design consisting of one group pre-test and post-test. A total of 38 students from Class IX A at SMPN 1 Gondang were selected purposively. Data were obtained through oral tests before and after the use of the ELSA Speak application. Data analysis was conducted using SPSS paired sample t-test, normality test, and homogeneity test. The study findings showed a significant increase in students' average performance scores, which increased from 60.65 (pre-test) to 73.82 (post-test). The statistical analysis of the paired sample t-test yielded a significance level below 0.05, indicating that the ELSA Speak application is effective in improving the English language skills of ninth-grade students at SMPN 1 Gondang. According to research findings, the ELSA Speak app is a useful resource for significantly improving students' English pronunciation. To provide creative and inspiring learning opportunities for students, it is recommended that technology-based resources like ELSA Speak be incorporated into language learning curriculum.